Being ethical and bioethical in daily life of primary health care: nurses' perceptions - Lívia Silveira Silva; Rosane Gonçalves Nitschke; Marta Inês Machado Verdi; Adriana Dutra Tholl; Fernanda Moura Lanza; Patrícia Peres de Oliveira; Selma Maria da Fonseca Viegas
ABSTRACT Objectives: to understand the perceptions of ethics and bioethics and how to be ethical and bioethical in daily life of Primary Health Care, from the perspective of nurses. Methods: this is a Holistic-qualitative Multiple Case Study, based on Comprehensive Everyday Sociology, with 54 participants. Results: two subcategories and the category Being ethical and bioethical in daily life of PHC: nurses' perceptions emerged. The ethical and bioethical being permeates a subjective and abstract self, whose fears, anxieties and concerns are intertwined with the human and professional dimensions in daily work and in personal-professional relationship. Ethics and bioethics perceptions emerge from subjectivity, established relationships, lived experiences and daily actions of nurses essential to the profession, professionals and individuals to be cared for. Final Considerations: ethical and bioethical perceptions and attitudes are essential to care, management and organizational actions, health care, and the safety of users and professionals.